Peningkatan Kapasitas Produksi dan Strategi Branding Produk Unggulan Daerah Berbasis Singkong dan Pisang di Desa Tugurejo, Ponorogo - Rashda Diana; M. Akhlis Azamuddin Tifani; Nouma Zidan Akbar; Nashruddin Sulthon; Muhammad Rizky Zulaini; Adib Sayyid Anam; Ahmad Nur Fajar Dwi Prakosa; Riyan Abdul Rosyid; Ahmad Faiq Noerjantoro; Raffa Arvel Nafi' Nadindra; Ahmad Fajri Rahmadi; Ahmad Rifki Humaidi; Yogi Banar Sasongko (Abdimas Indonesian Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) producing banana chips are one of the industrial sectors with high economic potential in Indonesia. This study aims to improve the competitiveness of Sale Pisang Bu Mul, a home-based product from Tugurejo, Ponorogo. It also analyzes the development strategies of MSMEs producing banana chips through product innovation and the use of digital marketing to increase competitiveness and revenue. The research method used is a descriptive qualitative approach, incorporating literature studies and observations of MSMEs. The results indicate that innovative flavor variants, improved packaging, product certification, and the use of social media and marketplaces can increase market reach and product added value. Digitalization is a factor that can expand the market in the digital economy era. This study recommends improving human resource capacity, access to financing, and collaboration with the government and digital platforms for business sustainability.